move all postulates to one module
[~helmut/bidiragda.git] / LiftGet.agda
1 module LiftGet where
2
3 open import Data.Unit using (⊤ ; tt)
4 open import Data.Nat using (ℕ ; suc)
5 open import Data.Vec using (Vec ; toList ; fromList) renaming ([] to []V ; _∷_ to _∷V_)
6 open import Data.List using (List ; [] ; _∷_ ; length ; replicate ; map)
7 open import Data.List.Properties using (length-map)
8 open import Data.Product using (∃ ; _,_ ; proj₁ ; proj₂)
9 open import Function using (_∘_ ; flip ; const)
10 open import Relation.Binary.Core using (_≡_)
11 open import Relation.Binary.PropositionalEquality using (_≗_ ; sym ; cong ; refl ; subst ; trans ; proof-irrelevance)
12 open Relation.Binary.PropositionalEquality.≡-Reasoning using (begin_ ; _≡⟨_⟩_ ; _∎)
13
14 import FreeTheorems
15 open FreeTheorems.ListList using (get-type ; free-theorem)
16 open FreeTheorems.VecVec using () renaming (get-type to getV-type)
17
18 getVec-to-getList : {getlen : ℕ → ℕ} → (getV-type getlen) → get-type
19 getVec-to-getList get = toList ∘ get ∘ fromList
20
21 getList-to-getlen : get-type → ℕ → ℕ
22 getList-to-getlen get = length ∘ get ∘ flip replicate tt
23
24 replicate-length : {A : Set} → (l : List A) → map (const tt) l ≡ replicate (length l) tt
25 replicate-length [] = refl
26 replicate-length (_ ∷ l) = cong (_∷_ tt) (replicate-length l)
27
28 getList-length : (get : get-type) → {B : Set} → (l : List B) → length (get l) ≡ getList-to-getlen get (length l)
29 getList-length get l = begin
30   length (get l)
31     ≡⟨ sym (length-map (const tt) (get l)) ⟩
32   length (map (const tt) (get l))
33     ≡⟨ cong length (sym (free-theorem get (const tt) l)) ⟩
34   length (get (map (const tt) l))
35     ≡⟨ cong (length ∘ get) (replicate-length l) ⟩
36   length (get (replicate (length l) tt)) ∎
37
38 length-toList : {A : Set} {n : ℕ} → (v : Vec A n) → length (toList v) ≡ n
39 length-toList []V = refl
40 length-toList (x ∷V xs) = cong suc (length-toList xs) 
41
42 toList-fromList : {A : Set} → (l : List A) → toList (fromList l) ≡ l
43 toList-fromList []       = refl
44 toList-fromList (x ∷ xs) = cong (_∷_ x) (toList-fromList xs)
45
46 toList-subst : {A : Set} → {n m : ℕ} (v : Vec A n) → (p : n ≡ m) → toList (subst (Vec A) p v) ≡ toList v
47 toList-subst v refl = refl
48
49 getList-to-getVec-length-property : (get : get-type) → {C : Set} → {m : ℕ} → (v : Vec C m) → length (get (toList v)) ≡ length (get (replicate m tt))
50 getList-to-getVec-length-property get {_} {m} v = begin
51     length (get (toList v))
52       ≡⟨ getList-length get (toList v) ⟩
53     length (get (replicate (length (toList v)) tt))
54       ≡⟨ cong (length ∘ get ∘ flip replicate tt) (length-toList v) ⟩
55     length (get (replicate m tt)) ∎
56
57 getList-to-getVec : get-type → ∃ λ (getlen : ℕ → ℕ) → (getV-type getlen)
58 getList-to-getVec get = getlen , get'
59   where getlen : ℕ → ℕ
60         getlen = getList-to-getlen get
61         get' : {C : Set} {m : ℕ} → Vec C m → Vec C (getlen m)
62         get' {C} v = subst (Vec C) (getList-to-getVec-length-property get v) (fromList (get (toList v)))
63
64 subst-subst : {A : Set} (T : A → Set) {a b c : A} → (p : a ≡ b) → (p' : b ≡ c) → (x : T a)→ subst T p' (subst T p x) ≡ subst T (trans p p') x
65 subst-subst T refl p' x = refl
66
67 subst-fromList : {A : Set} {x y : List A} → (p : y ≡ x) → subst (Vec A) (cong length p) (fromList y) ≡ fromList x
68 subst-fromList refl = refl
69
70 get-commut-1 : (get : get-type) {A : Set} → (l : List A) → fromList (get l) ≡ subst (Vec A) (sym (getList-length get l)) (proj₂ (getList-to-getVec get) (fromList l))
71 get-commut-1 get {A} l = begin
72   fromList (get l)
73     ≡⟨ sym (subst-fromList (cong get (toList-fromList l))) ⟩
74   subst (Vec A) (cong length (cong get (toList-fromList l))) (fromList (get (toList (fromList l))))
75     ≡⟨ cong (flip (subst (Vec A)) (fromList (get (toList (fromList l))))) (proof-irrelevance (cong length (cong get (toList-fromList l))) (trans p p')) ⟩
76   subst (Vec A) (trans p p') (fromList (get (toList (fromList l))))
77     ≡⟨ sym (subst-subst (Vec A) p p' (fromList (get (toList (fromList l))))) ⟩
78   subst (Vec A) p' (subst (Vec A) p (fromList (get (toList (fromList l)))))
79     ≡⟨ refl ⟩
80   subst (Vec A) p' (proj₂ (getList-to-getVec get) (fromList l)) ∎
81     where p : length (get (toList (fromList l))) ≡ length (get (replicate (length l) tt))
82           p = getList-to-getVec-length-property get (fromList l)
83           p' : length (get (replicate (length l) tt)) ≡ length (get l)
84           p' = sym (getList-length get l)
85
86 get-trafo-1 : (get : get-type) → {B : Set} → getVec-to-getList (proj₂ (getList-to-getVec get)) {B} ≗ get {B}
87 get-trafo-1 get {B} l = begin
88   getVec-to-getList (proj₂ (getList-to-getVec get)) l
89     ≡⟨ refl ⟩
90   toList (proj₂ (getList-to-getVec get) (fromList l))
91     ≡⟨ refl ⟩
92   toList (subst (Vec B) (getList-to-getVec-length-property get (fromList l)) (fromList (get (toList (fromList l)))))
93     ≡⟨ toList-subst (fromList (get (toList (fromList l)))) (getList-to-getVec-length-property get (fromList l)) ⟩
94   toList (fromList (get (toList (fromList l))))
95     ≡⟨ toList-fromList (get (toList (fromList l))) ⟩
96   get (toList (fromList l))
97     ≡⟨ cong get (toList-fromList l) ⟩
98   get l ∎
99
100 vec-len : {A : Set} {n : ℕ} → Vec A n → ℕ
101 vec-len {_} {n} _ = n
102
103 length-replicate : {A : Set} {a : A} → (n : ℕ) → length (replicate n a) ≡ n
104 length-replicate 0       = refl
105 length-replicate (suc n) = cong suc (length-replicate n)
106
107 subst-cong : {A : Set} → (T : A → Set) → {g : A → A} → {a b : A} → (f : {c : A} → T c → T (g c)) → (p : a ≡ b) → f ∘ subst T p ≗ subst T (cong g p) ∘ f
108 subst-cong T f refl _ = refl
109
110 fromList-toList : {A : Set} {n : ℕ} → (v : Vec A n) → fromList (toList v) ≡ subst (Vec A) (sym (length-toList v)) v
111 fromList-toList     []V       = refl
112 fromList-toList {A} (x ∷V xs) = begin
113   x ∷V fromList (toList xs)
114     ≡⟨ cong (_∷V_ x) (fromList-toList xs) ⟩
115   x ∷V subst (Vec A) (sym (length-toList xs)) xs
116     ≡⟨ subst-cong (Vec A) (_∷V_ x) (sym (length-toList xs)) xs ⟩
117   subst (Vec A) (cong suc (sym (length-toList xs))) (x ∷V xs)
118     ≡⟨ cong (λ p →  subst (Vec A) p (x ∷V xs)) (proof-irrelevance (cong suc (sym (length-toList xs))) (sym (cong suc (length-toList xs)))) ⟩
119   subst (Vec A) (sym (length-toList (x ∷V xs))) (x ∷V xs) ∎
120
121 get-commut-2 : (getlen : ℕ → ℕ) → (get : getV-type getlen) → {B : Set} {n : ℕ} → (toList ∘ get {B} {n}) ≗ (getVec-to-getList get) ∘ toList
122 get-commut-2 getlen get {B} v = begin
123   toList (get v)
124     ≡⟨ sym (toList-subst (get v) (cong getlen (sym (length-toList v)))) ⟩
125   toList (subst (Vec B) (cong getlen (sym (length-toList v))) (get v))
126     ≡⟨ cong toList (sym (subst-cong (Vec B) get (sym (length-toList v)) v)) ⟩
127   toList (get (subst (Vec B) (sym (length-toList v)) v))
128     ≡⟨ cong (toList ∘ get) (sym (fromList-toList v)) ⟩
129   toList (get (fromList (toList v))) ∎
130
131 get-trafo-2-getlen : (getlen : ℕ → ℕ) → (get : getV-type getlen) → proj₁ (getList-to-getVec (getVec-to-getList get)) ≗ getlen
132 get-trafo-2-getlen getlen get n = begin
133   proj₁ (getList-to-getVec (getVec-to-getList get)) n
134     ≡⟨ refl ⟩
135   length (toList (get (fromList (replicate n tt))))
136     ≡⟨ length-toList (get (fromList (replicate n tt))) ⟩
137   vec-len (get (fromList (replicate n tt)))
138     ≡⟨ cong getlen (length-replicate n) ⟩
139   getlen n ∎
140
141 get-trafo-2-get : (getlen : ℕ → ℕ) → (get : getV-type getlen) → {B : Set} {n : ℕ} → proj₂ (getList-to-getVec (getVec-to-getList get)) ≗ subst (Vec B) (sym (get-trafo-2-getlen getlen get n)) ∘ get
142 get-trafo-2-get getlen get {B} {n} v = begin
143   proj₂ (getList-to-getVec (getVec-to-getList get)) v
144     ≡⟨ refl ⟩
145   subst (Vec B) p (fromList (toList (get (fromList (toList v)))))
146     ≡⟨ cong (subst (Vec B) p) (fromList-toList (get (fromList (toList v)))) ⟩
147   subst (Vec B) p (subst (Vec B) p' (get (fromList (toList v))))
148     ≡⟨ subst-subst (Vec B) p' p (get (fromList (toList v))) ⟩
149   subst (Vec B) (trans p' p) (get (fromList (toList v)))
150     ≡⟨ cong (subst (Vec B) (trans p' p) ∘ get) (fromList-toList v) ⟩
151   subst (Vec B) (trans p' p) (get (subst (Vec B) (sym (length-toList v)) v))
152     ≡⟨ cong (subst (Vec B) (trans p' p)) (subst-cong (Vec B) get (sym (length-toList v)) v) ⟩
153   subst (Vec B) (trans p' p) (subst (Vec B) (cong getlen (sym (length-toList v))) (get v))
154     ≡⟨ subst-subst (Vec B) (cong getlen (sym (length-toList v))) (trans p' p) (get v) ⟩
155   subst (Vec B) (trans (cong getlen (sym (length-toList v))) (trans p' p)) (get v)
156     ≡⟨ cong (flip (subst (Vec B)) (get v)) (proof-irrelevance (trans (cong getlen (sym (length-toList v))) (trans p' p)) p'') ⟩
157   subst (Vec B) p'' (get v) ∎
158     where n' : ℕ
159           n' = length (toList (get (fromList (replicate n tt))))
160           p : length (toList (get (fromList (toList v)))) ≡ n'
161           p = getList-to-getVec-length-property (getVec-to-getList get) v
162           p' : getlen (length (toList v)) ≡ length (toList (get (fromList (toList v))))
163           p' = sym (length-toList (get (fromList (toList v))))
164           p'' : getlen n ≡ n'
165           p'' = sym (get-trafo-2-getlen getlen get (vec-len v))